2020
DOI: 10.1177/2325967120958007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Structural Subscapularis Integrity After Latarjet Procedure Versus Iliac Crest Bone Graft Transfer

Abstract: Background: Although clinical outcome scores are comparable after coracoid transfer procedure (Latarjet) and iliac crest bone graft transfer (ICBGT) for anterior shoulder instability with glenoid bone loss, a significant decrease in internal rotation capacity has been reported for the Latarjet procedure. Hypothesis: The subscapularis (SSC) musculotendinous integrity will be less compromised by ICBGT than by the Latarjet procedure. Study Design: Cohort study; Level of evidence, 3. Methods: We retrospectively an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…36 Besides this stabilizing effect, there are concerns that this permanent redirection of the muscle and tendon may jeopardize subscapularis structure and function. 31 Although the consequence of this redirection may solely be altering the moment arm of the subscapularis, the integrity of the inferior half of the subscapularis is without any doubt one of the prerequisites of a stable and functioning glenohumeral joint. 10,11 The Latarjet procedure was reported to be associated with varying loss of glenohumeral rotation strength.…”
Section: Discussionmentioning
confidence: 99%
“…36 Besides this stabilizing effect, there are concerns that this permanent redirection of the muscle and tendon may jeopardize subscapularis structure and function. 31 Although the consequence of this redirection may solely be altering the moment arm of the subscapularis, the integrity of the inferior half of the subscapularis is without any doubt one of the prerequisites of a stable and functioning glenohumeral joint. 10,11 The Latarjet procedure was reported to be associated with varying loss of glenohumeral rotation strength.…”
Section: Discussionmentioning
confidence: 99%
“…Siegert et al. 22 retrospectively compared the changes to the subscapularis muscle in patients who underwent an iliac crest bone graft to the anterior glenoid and patients who were treated with a Latarjet procedure. They found that the progress of fatty infiltration of the subscapularis muscle and the rerouting angle of the muscle were significantly higher for Latarjet patients on CT scans, and this correlated with a lower capacity of internal rotation.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 13 , 19 , 21 Moreover, due to the permanent split of the subscapularis, weakness and muscle atrophy with fatty degeneration of the inferior part of the muscle itself have been described. 22 , 23 …”
mentioning
confidence: 99%
“…Lastly, a potential benefit of avoiding a sling postoperatively is the prevention of muscle atrophy. Recent studies suggested a negative impact on internal rotation at 90° of abduction after the Latarjet procedure secondary to subscapularis rerouting compared to iliac bone grafts ( 42 , 60 ).…”
Section: Discussionmentioning
confidence: 99%